Asymmetric synthesis of N–N axially chiral compounds via organocatalytic atroposelective N-acylation. Issue 1 (6th December 2021) - Lin, Wei; Zhao, Qun; Li, Yao; Pan, Ming; Yang, Chen; Yang, Guo-Hui; Li, Xin
Abstract : A highly efficient atroposelective N -acylation reaction of quinazolinone type benzamides with cinnamic anhydrides for the direct catalytic synthesis of optically active atropisomeric quinazolinone derivatives was developed. Abstract : Compared with the well-developed C–C and C–N axial chirality, the asymmetric synthesis of N–N axial chirality remains elusive and challenging. Herein we report the first atroposelective N -acylation reaction of quinazolinone type benzamides with cinnamic anhydrides for the direct catalytic synthesis of optically active atropisomeric quinazolinone derivatives. This reaction features mild conditions and a broad substrate scope and produces N–N axially chiral compounds with high yields and very good enantioselectivities. Besides, the synthetic utility of the protocol was proved by a large scale reaction, transformation of the product and the utilization of the product as an acylation kinetic resolution reagent. Moreover, DFT calculations provide convincing evidence for the interpretation of stereoselection.